PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ARTICULATE STORYLINE PADA MATERI VIRUS UNTUK SISWA KELAS X IPA SMA - Maak, Yohanis Doki; Shidik, Muhammad Amran; Sila, Vinsensia Ulia Rita (BIOEDUKASI (Jurnal Pendidikan Biologi), 2024)
This research is motivated by the learning resources used that do not fully support the needs of students and also the limited laboratory facilities at school to observe viruses are not yet available. The purpose of this study was to develop learning resources in the form of interactive multimedia based on Articulate Storyline on virus material for class X IPA students of Senior High School (SMAS Pelita Karya) and test the feasibility of interactive multimedia. This research uses the type of research and development (R&D), but in this research process, it only reaches the feasibility test by experts and does not reach the student trial stage. The data source in this study is the validation results obtained from 2 media experts, 1 material expert, and 2 experts on the feasibility of Biology learning media. The data obtained were then analyzed and presented in the form of tables and figures. The validation results from the first media expert obtained an overall average of 4.56 aspects with the category "Very Feasible", and the evaluation results from the second media expert obtained an average of 4.56 with the category "Very Feasible". The results of validation from material experts obtained an overall average aspect of 4.33 with the category "Very Feasible". The validation results from the first Biology learning media feasibility expert obtained an overall average of 4.00 aspects with the category "Feasible", for the assessment results from the second Biology learning media feasibility expert obtained an overall average of 4.70 aspects with the category "Very Feasible". The assessment results from the validators show that interactive multimedia based on Articulate Storyline on virus material is very feasible to use as learning media.